Tourists Motivations in Visiting Buddhist Temples of Yogyakarta - Arina Afiyati (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study aims to explore the underlying motivations of tourists visiting Buddhist temples in Yogyakarta, Indonesia. The research focuses on identifying and analyzing the differences in motivation between male and female tourists. Research methods: A qualitative approach was employed, using questionnaires, interviews, and documentation. Data were collected from domestic and international tourists at four Buddhist temples namely Kalasan Temple, Sari Temple, Banyunibo Temple, and Sewu Temple and then analyzed using the Miles and Huberman model. Results and discussion: The study reveals six major types of tourist motivation: physical, cultural, interpersonal/social, fantasy, prestige/status, and wish-fulfillment. While both male and female tourists shared these motivations, significant differences were observed in their intensity. Female tourists showed higher motivation in physical, cultural, and emotional aspects, while male tourists were more driven by status and the pursuit of personal aspirations. Cultural motivation emerged as the strongest factor overall, even though it is not listed in Ryan’s (1991) original classification. Gender also influenced specific motivational patterns, such as preferences for spiritual experiences, cultural exploration, and recreational activities. Implication: Understanding tourist motivation, especially across gender lines, can help tourism stakeholders design more targeted and meaningful experiences. This insight supports the development of culturally sensitive, gender-responsive, and sustainable religious tourism in heritage sites like Buddhist temples.